2021
DOI: 10.1111/jerd.12837
|View full text |Cite
|
Sign up to set email alerts
|

External gap progression after cyclic fatigue of adhesive overlays and crowns made with high translucency zirconia or lithium silicate

Abstract: Objectives To evaluate three‐dimensional external gap progression after chewing simulation of high translucency zirconia (HTZ) and zirconia‐reinforced lithium silicate (ZLS) applied on endodontically treated teeth with different preparation designs. Materials and Method Endodontically treated molars were prepared with low‐retentive (adhesive overlay) and high‐retentive (full crown) designs above cementum‐enamel junction and restored with HTZ and ZLS. Micro‐computed tomography analysis was assessed before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Among polished samples, compared with the situation before aging, the paired t -Test (α = 0.05) reported that the surface roughness values for ST ( p < 0.005) increased more than those for CE ( p > 0.005) and among materials, the highest Ra values were measured for ST (0.052 to 0.054) and the lowest for CE (0.047 to 0.048); for IP, the values tend to decrease from the cervical (0.053 ± 0.009) to incisal (0.049 ± 0.009) area. This means that the material with 4 mol% Yttrium content is more susceptible to the aging process, thus hydrothermal and mechanical impact cause phase transformation, resulting in surface degradation and an increase in microhardness; this situation has been presented in other studies [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 71%
“…Among polished samples, compared with the situation before aging, the paired t -Test (α = 0.05) reported that the surface roughness values for ST ( p < 0.005) increased more than those for CE ( p > 0.005) and among materials, the highest Ra values were measured for ST (0.052 to 0.054) and the lowest for CE (0.047 to 0.048); for IP, the values tend to decrease from the cervical (0.053 ± 0.009) to incisal (0.049 ± 0.009) area. This means that the material with 4 mol% Yttrium content is more susceptible to the aging process, thus hydrothermal and mechanical impact cause phase transformation, resulting in surface degradation and an increase in microhardness; this situation has been presented in other studies [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 71%
“…made the comparison with previous studies more challenging. Additionally, specimens were tested as sintered and were not subjected to cyclic fatigue that could show different types of marginal adaptation [ 59 ]. Therefore, the authors recommend testing more brands of 3D-printed zirconia crowns and different additive manufacturing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The Cerec system was initially developed with the aim of completing a dental ceramic restoration in a single appointment [ 1 , 2 , 3 ], with the entire manufacturing process carried out within the dental office. Ongoing improvements in this system have led to a wider acceptance in dental practice [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%